The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fvets.2021.605286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Latex of Synadenium grantii Hook F. (Euphorbiaceae) on a Preclinical Model of Canine Prostate Cancer

Abstract: Prostatic cancer (PC) stands out in terms of its occurrence, pathophysiology, and unfavorable prognostics in humans and dogs. Natural drugs bear an integrative potential for conventional antineoplastic treatments. In this context, the bioproducts of Synadenium grantii have been empirically used in different parts of Brazil for the integrative treatment of prostate cancer in humans. However, there is no availability of scientific evidence of the antitumor effects of S. grantii. Therefore, this study aimed to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…The difference in pH, based on the results obtained does not show great impact, leaving both JB (Synadenium Umbellatur) and JC (Sinadenium grantii) with similar values and classifying with the same pH according to the reference scale, such as 4.71±1.015 and 4.19±0.34 respectively. In this acidic way, that is, these values do not favor pathogenic bacterial growth, similar, since there was no statistical difference at the level of 5% significance from one variety to the other, these results are in agreement with what is cited by Brito et al (2021), who state in their studies that these pH values provide balance to the product after its removal from the stem, thus delaying microbial development and multiplication.…”
Section: Physicochemical Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference in pH, based on the results obtained does not show great impact, leaving both JB (Synadenium Umbellatur) and JC (Sinadenium grantii) with similar values and classifying with the same pH according to the reference scale, such as 4.71±1.015 and 4.19±0.34 respectively. In this acidic way, that is, these values do not favor pathogenic bacterial growth, similar, since there was no statistical difference at the level of 5% significance from one variety to the other, these results are in agreement with what is cited by Brito et al (2021), who state in their studies that these pH values provide balance to the product after its removal from the stem, thus delaying microbial development and multiplication.…”
Section: Physicochemical Characterizationsupporting
confidence: 91%
“…The same result was found for the determination of acidity, where Table 2 shows that all analyses showed the same result, as shown in the example. Acidity is a parameter used to guide the quality of the sample, that is, an excellent and very important tool to determine signs of the presence of organic acids, as mentioned by Brito et al (2021), which is not indicated by the results in Table 2.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…Latex from Euphorbia umbellata exhibited cytotoxicity activity against HeLa and HRT-18 cells, melanoma cells (B16F10), and hepatocellular carcinoma. Additionally, in an in vivo study, minimization tumor mass in mice was observed with latex application [ 13 ]. Recently, numerous natural flavonoids such as epicatechin, luteolin, rutin, quercetin, naringenin, hesperidin, baicalin, and diosmin were applied for the management of SARS-CoV-2 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two prostate cell (PC) cultures were established from intact dogs with non-metastatic PC (PC1) and with metastatic PC (PC2). All of the tested latex concentrations had an effect on both PC1 and PC2 cells in a dose-dependent manner ( Brito et al., 2021 ). It is also crucial to note the activity of proteins present in the Euphorbiaceae latex.…”
Section: Anticancer Properties Of Latex-bearing Plant Extractsmentioning
confidence: 99%